2022
DOI: 10.3390/genes13030533
|View full text |Cite
|
Sign up to set email alerts
|

Circum-Saharan Prehistory through the Lens of mtDNA Diversity

Abstract: African history has been significantly influenced by the Sahara, which has represented a barrier for migrations of all living beings, including humans. Major exceptions were the gene flow events that took place between North African and sub-Saharan populations during the so-called African Humid Periods, especially in the Early Holocene (11.5 to 5.5 thousand years ago), and more recently in connection with trans-Saharan commercial routes. In this study, we describe mitochondrial DNA (mtDNA) diversity of human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
(90 reference statements)
1
8
0
Order By: Relevance
“…Genetic analyses generally revealed weak population structure, with most of the variation found within groups rather than between groups ( Čížková et al 2017 ; Nováčková et al 2020 ; Diallo et al 2022 ; Fortes-Lima et al 2022 ). Depending on subsistence strategy, different distributions of uniparental markers have been observed in the Sahel.…”
Section: Pervasive Admixture In Africa During the Past 10000 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses generally revealed weak population structure, with most of the variation found within groups rather than between groups ( Čížková et al 2017 ; Nováčková et al 2020 ; Diallo et al 2022 ; Fortes-Lima et al 2022 ). Depending on subsistence strategy, different distributions of uniparental markers have been observed in the Sahel.…”
Section: Pervasive Admixture In Africa During the Past 10000 Yearsmentioning
confidence: 99%
“…Whereas sedentary farmers are stratified based on geography but not linguistics, the opposite is true for western Fulani pastoralists ( Nováčková et al 2020 ). Furthermore, Y chromosomal haplogroups are genetically more diverse in nomadic pastoralists groups, whereas mtDNA haplogroups are more diverse in sedentary farmers ( Čížková et al 2017 ; Nováčková et al 2020 ; Diallo et al 2022 ). It has been suggested that low levels of sex-biased gene flow with sedentary farmers caused the Fulani to lose mtDNA diversity ( Čížková et al 2017 ).…”
Section: Pervasive Admixture In Africa During the Past 10000 Yearsmentioning
confidence: 99%
“…The population history of the Sahel/Savannah belt has been studied thus far mainly through genetic variation of the uniparental markers ( Pereira et al 2010 ; Černý et al 2011 ; Nováčková et al 2020 ; Diallo et al 2022 ), or specific genes, such as LCT , NAT2 , TAS2R16 , or HLA-B ( Podgorná et al 2015 ; Triska et al 2015 ; Sanchez-Mazas et al 2017 ; Vicente et al 2019 ; Priehodová et al 2020 ; Kulichová et al 2021 ). It has been shown that the genetic differentiation among pastoralists and farmers does not represent significant population structure and that intensive gene-flow or shared ancestry might be among the possible reasons for this ( Černý et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, all sampled local populations of the Fulani pastoralists (collected between Senegal and Chad) have very similar genetic components, and also show genetic affinities with other western African groups. They also have a non-negligible Eurasian contribution (∼20%) that is missing in neighboring western African populations ( Triska et al 2015 ; Vicente et al 2019 ; Nováčková et al 2020 ; Diallo et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other differences between the pastoralists and the farmers in the Sahel belt can be demonstrated in the degree of inbreeding. The farmers tend to practice exogamy, while the pastoralists practice endogamy, which manifests itself among other things by a reduction of several genetic diversity measures in the mtDNA genome (such as gene diversity, nucleotide diversity, and the mean number of pairwise differences) of pastoralists analysed so far [ 69 ]. This finding is most evident in the Rashaayda Arab population from eastern Sudan, whose founders emigrated to the Sahel belt just ~150 years ago from Saudi Arabia [ 70 ].…”
Section: The Contribution Of Population Genetics To Disentangling Hum...mentioning
confidence: 99%